6.3k views
5 votes
Please help. Use the steps to finish writing an equivalent equation for y in terms of x. −6x = 12 − 4y 1.  Subtract 12 from both sides: −6x − 12 = −4y 2.  Divide −4 to both sides: −6x − 12 −4 = −4y −4 x + 3 = y

User Claud
by
5.7k points

2 Answers

2 votes

Answer:

y = 1.5x + 3

Explanation:

= - 6x - 12 = - 4y

(- 6x - 12)/- 4 = - 4y/- 4

1.5x + 3 = y

Hope this helps!

User Erazihel
by
4.9k points
6 votes

Answer:

3/2 x +3 = y

Explanation:

−6x = 12 − 4y

Subtract 12 from both side

−6x-12 = 12 − 4y-12

-6x -12 = -4y

Divide both side by -4

(-6x -12)/-4 = -4y/-4

-6x/-4 -12/-4 = y

3/2 x +3 = y

User Adaephon
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.